A8.10 The effect of rituximab treatment on B and T cell subsets in lymphoid tissues of patients with rheumatoid arthritis. (13th February 2015) - Ramwadhdoebe, TH; Boumans, MJH; Bruijnen, STG; Safy, M; Berger, FH; van Baarsen, LGM; van der Laken, CJ; Gerlag, DM; Thurlings, RM; Tak, PP
Abstract : Background: Rheumatoid arthritis (RA) is characterised by the presence of autoantibodies and infiltration of B and T-cells in synovial joints. Accordingly, targeting B-cells by rituximab treatment has been shown to be beneficial for a subset of RA patients. Despite a rapid depletion of B-cells in peripheral blood, B-cells may persist in synovial tissue and bone marrow. Since B-cell differentiation occurs in secondary lymphoid tissue we investigated the effect of rituximab treatment on B and T-cell subsets in lymphoid biopsies of RA patients. Methods: Fourteen patients with active RA (baseline Disease Activity Score 28 joint assessment (DAS28) was 5.3 (4.7–6.0 [median, IQR]) were treated with intravenous infusions of 1000 mg of rituximab on day 1 and day 15. Premedication with methylprednisolone was omitted to study the specific effects of rituximab. Ultrasound-guided inguinal lymph node biopsies were obtained before start of rituximab treatment and four weeks after the first infusion and immediately processed for flow cytometry analyses. For comparison 5 lymph node biopsies from healthy controls were analysed. Results: Lymph node B-cell subsets in RA patients were not significantly increased compared to healthy controls, while frequencies of early activated T-cells, CD3 + CD69 + and CD3 + CD25 + CD69 + were significantly increased (p = 0.01 and p = 0.02 respectively). The frequencies of switched memory B-cells (CD27 + IgD - ) correlated significantly with the frequency of early activated T-cells (CD3 + CD69 + p = 0.02, r = 0.65; CD3 + CD25 + CD69 + p = 0.002, r = 0.80). EULAR response after 24 weeks was as follows: 29% good, 50% moderate and 21% non-responders. Four weeks after treatment there was a complete depletion of B-cells in peripheral blood (cut off < 0.0001 × 10 9 /Litre) in 9 of the 13 patients measured. In lymph nodes, 4 weeks after rituximab treatment, total CD19 + B-cells were significantly but incompletely depleted (p = 0.0004). CD19 frequency before treatment was 21.3% (13.8–32.4 [median, IQR]) and CD19 frequency after treatment was 9.7% (1.3–14.9 [median, IQR]). Especially naive (CD27 - IgD + ; p = 0.0006) and unswitched memory B-cells (CD27 + IgD + ; p = 0.0012) significantly decreased, while switched memory B-cells (CD27 + IgD - ) and double negative B-cells (CD27 - IgD - ) persisted. Also, activated T-cells (CD3 + CD25 + CD69 + T; p = 0.03) significantly decreased. No correlation was found between lymphoid B or T-cell subset depletion and response to treatment. Conclusion: This study provides for the first time detailed insight in the effects of rituximab therapy on lymph node immune cells in RA patients. Of interest, rituximab not only affects the number of lymphoid B-cells but also reduced the number of activated lymphoid T-cells suggesting that lymphoid B-cells contribute to lymphoid T-cell activation in RA.